Biomolecular Markers within the Core Axis of Aging and Particulate Air Pollution Exposure in the Elderly: A Cross-Sectional Study - Pieters, Nicky (Environ Health Perspect, 2015)
BACKGROUND: Telomere length and mitochondrial DNA (mtDNA) content are markers of aging and aging-related diseases. There is inconclusive evidence concerning the mechanistic effects of airborne particulate matter (PM) exposure on biomolecular markers of aging. OBJECTIVE: The present study examines the association between short- and long-term PM exposure with telomere length and mtDNA content in the elderly and investigates to what extent this association is mediated by expression of genes playing a role in the telomere–mitochondrial axis of aging. METHODS: Among 166 nonsmoking elderly participants, we used qPCR to measure telomere length and mtDNA content in leukocytes and RNA from whole blood to measure expression of SIRT1, TP53, PPARGC1A, PPARGC1B, NRF1, and NFE2L2. Associations between PM exposure and markers of aging were estimated using multivariable linear regression models adjusted for sex, age, BMI, socioeconomic status, statin use, past smoking status, white blood cell count, and percentage of neutrophils. Mediation analysis was performed to explore the role of age-related markers between the association of PM exposure and outcome. Annual PM2.5 exposure was calculated for each participant’s home address using a high-resolution spatial–temporal interpolation model. RESULTS: Annual PM2.5 concentrations ranged from 15 to 23 μg/m3. A 5-μg/m3 increment in annual PM2.5 concentration was associated with a relative decrease of 16.8% (95% CI: –26.0%, –7.4%, p = 0.0005) in telomere length and a relative decrease of 25.7% (95% CI: –35.2%, –16.2%, p < 0.0001) in mtDNA content. Assuming causality, results of the mediation analysis indicated that SIRT1 mediated 19.5% and 22.5% of the estimated effect of PM2.5 exposure on telomere length and mtDNA content, respectively. CONCLUSIONS: Our findings suggest that the estimated effects of PM2.5 exposure on the telomere–mitochondrial axis of aging may play an important role in chronic health effects of PM2.5. CITATION: Pieters N, Janssen BG, Dewitte H, Cox B, Cuypers A, Lefebvre W, Smeets K, Vanpoucke C, Plusquin M, Nawrot TS. 2016. Biomolecular markers within the core axis of aging and particulate air pollution exposure in the elderly: a cross-sectional study. Environ Health Perspect 124:943–950; http://dx.doi.org/10.1289/ehp.1509728